The Role of The Village Head in The Development of The Joint Business Group for Poor Peoples Toward Poverty Alleviation - Susilo Wdodo; Rijel Samaloisa (Asian Social Work Journal, 2022)
Poverty in Widodomartani is still classified as high poverty for about 9 % of its villagers. Central, local, and the village-level government tried to solve this issue. In 2013, Widodomartani Village received some programs to control the poverty from Indonesia Ministry of Social Affair launching the Kelompok Usaha Bersama Fakir Miskin (KUBE FM) program. The implementation of the KUBE FM Program needs assistance from all parties, thus it can be going well. Widodomatani Village-head (Lurah) is one of the policymakers who can assist the KUBE FM Program. The village head has some authority to run the program, one of which is society’s empowerment. Hence, the village head’s assistance in KUBE FM Program could help reduce and/or remove poverty in Widodomartani.